Approaching Socially Responsible Investment with a Comprehensive Ratings Scheme: Total Social Impact - Dillenburg, Stephen (Journal of business ethics, 2003)
The socially responsible investment industry (SRI) is slowly changing from a screening, avoidance paradigm to a comprehensive paradigm that seeks to affect corporate behavior. Credible rating systems are a key component of this sea change. Reliable and recognizable social and environmental metrics are critical to this progress. The Total Social Impact (TSI) rating approach is a new social metric scheme based on a comprehensive rating of stakeholder issues. This paper describes the evolution of SRI ratings and the role that TSI hopes to play in affecting business behavior by promoting principled business leadership.